Zirconium phosphate based proton conducting membrane for DMFC application. (10th August 2015) - Pandey, Jay; Seepana, Murali Mohan; Shukla, Anupam
Abstract: A proton conducting poly(vinylidene fluoride) (PVDF) supported zirconium phosphate (ZrP) ion-exchange membrane (ZrP/PVDF) was synthesized for potential application in DMFC by filling the pores of a PVDF film with in-situ grown ZrP particles. Presence of labile protons attached to PO group was confirmed from 1 H NMR and FT-IR characterizations. SEM micrographs showed defect-free top surface. The thermal stability and mechanical strength of the ZrP/PVDF membrane was better than Nafion-117. Water to methanol uptake ratio was higher while methanol cross-over for ZRP/PVDF membrane was lower than Nafion-117. Membrane possessed fair electrochemical properties; 0.85 static counter-ion transport number, 0.76 meqg −1 ion exchange capacity and 1.25 mScm −1 proton conductivity at 30 °C. DMFC performance of the synthesized membrane at 35 °C was compared with the Nafion-117. DMFC studies were also done at different operating conditions and the maximum peak power density was 32.3 mWcm −2 at 60 °C, 1 M methanol concentration and 60% relative humidity. Highlights: ZrP/PVDF membrane was synthesized via in-situ method. Membrane exhibited excellent thermal stability of up to 380 °C. Membrane has lower methanol permeability compared to Nafion-117. Maximum power density was 32.3 mWcm −2 at 60 °C.